Optimalisasi Troubleshooting Sistem TI Melalui SOP - Birrul Walidain Al Musthofa; Fajar Annas Susanto; Endang Sulistiyani; Tri Deviasari Wulan; Dike Bayu Magfira (JURNAL TECNOSCIENZA, 2026)
Information technology systems play an important role in supporting company operations. However, at PT Berlian Jasa Terminal Indonesia (BJTI), troubleshooting of IT devices was previously carried out incidentally without official documentation, making evaluation difficult and increasing downtime risk. This study aims to optimize troubleshooting activities through the development of new, structured, and documented Standard Operating Procedures (SOPs). The research method includes observation, analysis of existing conditions, troubleshooting workflow design, SOP development, and testing through logbook implementation. The results show that the new SOP makes the troubleshooting process more systematic, accountable, and easier to evaluate, while also reducing repair time and the number of device failures.